Do quality markers for health websites affect the perception of vaccination webpages?. (February 2017) - Allam, Ahmed; Sak, Gabriele; Diviani, Nicola; Schulz, Peter Johannes
Abstract: As people's health, and in some cases even their lives are at stake, the quality of health information on the web becomes a prime public health concern. Attempts at measuring or certifying quality usually use a set of quality markers, but their individual contribution to overall quality, and further to user perception and attitudes, is largely unknown. This study aims at assessing this contribution, using the topic of vaccination. It combines data from three sources, a survey participants filled in after completing an information search task, records of the webpages visited during that task, and a content analysis of these webpages determining the presence or absence of quality markers and the pages' tone towards vaccination. Results show that the tone of the webpages participants rated and were exposed to, is highly correlated with their attitude towards vaccination. Markers shown to be associated with high quality were also correlated with attitude, in particular when they were related to the quality of information content (such as "medical ownership", "specific accreditations" of health content and reporting "benefits of treatment/vaccination") rather than esthetic/visual and design markers. The results suggest that the approach to measuring the quality of health websites using such markers is both necessary and promising. Highlights: Not all quality markers are associated with positive tone towards vaccination. Tone of webpages rated by users correlates with their attitude toward vaccination. Content-related quality markers are considered more than visual and design markers. A small set of markers reduces the time for health websites quality evaluation.